(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this Paper model Will help to converts data coming from different social media sites , such as traditional blogging sites , e-mail sites , Social web pages of Face book and intelligent tutoring systems into information that may be useful for researchers, professors, institutions and students on understanding and evaluating educational systems, aiming for improving the quality of the educational process. For that matter, the educational data mining process aims for developing and applying computational approaches such as data mining, web mining, psychometrics and statistical techniques, for allowing the automatic information extraction from huge amounts of data.